TYPES AND FUNCTIONS IN MEASURING SUBJECTS OF E-COMMERCE E-MAIL: A PRAGMATICS STUDY - Nasstasya Ilona de Wannal; Heri Heryono (Universitas Widyatama, 2020)
Transaction of e-commerce is often used to refer to selling physical products online, but can also describe all types of commercial transactions that are facilitated through the internet. This study aims to describe the kinds of Speech Actions in the use of Language as the subject of E-Commerce E-Mail and identify the function of speech acts used in the subject of E-Commerce E-Mail. Advertising is manifested in various forms (declarative, interrogative, imperative or a combination thereof), but all of which state the request or function invite to do something. This is in accordance with the nature of advertising that is persuasive. Then, the variety of languages used is business variety, as well in general, advertisements are presented with simple language and sufficient style interesting, which among others looks at aspects of typography, poetic expressions, and use of repetitive. The method used in this study is a descriptive method. The researcher collects data containing Speech Acts on E-Mail E-Commerce, classifies data according to its type, analyzes data, then draws conclusions from the results of the study. The results of the study show that: (1) there are 4 types of speech acts found in this study, which are locutionary, illocutionary, perlocutionary and combinations and (2) speech act functions found in the analysis are dominated by representative functions.